Poster: Dynamic Analysis Using JavaScript Proxies - Christophe, Laurent; De Roover, Coen; De Meuter, Wolfgang (2015 IEEE/ACM 37th IEEE International Conference on Software Engineering, 2015)
JavaScript has become a popular programming language. However, its highly dynamic nature encumbers static analysis for quality assurance purposes. Only dynamic techniques such as concolic testing seem to cope. Often, these involve an instrumentation phase in which source code is extended with analysis-specific concerns. The corresponding implementations represent a duplication of engineering efforts. To facilitate developing dynamic analyses for JavaScript, we introduce Aran; a general-purpose JavaScript instrumenter that takes advantage of proxies, a recent addition to the JavaScript reflection APIs.